2022
DOI: 10.3389/fnbeh.2021.777911
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Masculinity and Spatial Skills Is Moderated by the Estrogenic and Progestational Activity of Oral Contraceptives

Abstract: Conversations about gender and spatial skills frequently dissolve into a hackneyed debate over nature and nurture. This is particularly true for conversations concerning three-dimensional (3D) mental rotations skill, which shows the largest gender difference of all aspects of cognition, with men—on average—outperforming women. To advance this empirical area of inquiry, biopsychosocial influences on spatial skills should be considered, and a unique opportunity do to that is provided by combined oral contracepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 67 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…A growing body of research supports the tenet that oral contraceptives impact cognition and alter brain function in task- and composition- dependent manners (e.g., Gogos, 2013 ; Egan and Gleason, 2012 ; Beltz et al, 2015 , 2022 ; Porcu et al, 2019 ; Taylor et al, 2020 ; Ycaza Herrera et al, 2020 ; Gravelsins et al, 2021 ; Lewis et al, 2022 ; Menting-Henry et al, 2022 ). Overall, the current series of experiments found that the spironolactone-derived progestin drospirenone has beneficial effects for spatial working memory performance in a young adult Ovx rat model, and that the synthetic estrogen EE has variable effects on behavior that depend on dose and combination with drospirenone.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research supports the tenet that oral contraceptives impact cognition and alter brain function in task- and composition- dependent manners (e.g., Gogos, 2013 ; Egan and Gleason, 2012 ; Beltz et al, 2015 , 2022 ; Porcu et al, 2019 ; Taylor et al, 2020 ; Ycaza Herrera et al, 2020 ; Gravelsins et al, 2021 ; Lewis et al, 2022 ; Menting-Henry et al, 2022 ). Overall, the current series of experiments found that the spironolactone-derived progestin drospirenone has beneficial effects for spatial working memory performance in a young adult Ovx rat model, and that the synthetic estrogen EE has variable effects on behavior that depend on dose and combination with drospirenone.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it was less innovative, and now more dated, in the design and labeling of gender scales with which participants scored themselves. In addition, we did not collect detailed data on hormonal birth control, menstrual cycle, and other factors that have since been suggested to have an influence on MRT performance (Beltz et al, 2022) but have yet to be included in studies of transgender identity. Nonetheless, despite these concerns, the more inclusive methods employed in our study produced different results from those using standard practices and provide new insight into the years in which transgender identity was increasing in visibility in public discourse.…”
Section: Limitationsmentioning
confidence: 99%
“…Indeed, various gender-sensitive facets of extraversion, agreeableness and neuroticism may not only be grouped according to the BIG-5, but also along the overarching dimensions of masculinity and femininity ( Gruber et al, 2019 ). Given that femininity in particular has been associated with gray matter volumes in prefrontal areas ( Pletzer, 2019 ), while masculinity has repeatedly been related to spatial abilities ( Reilly and Neumann, 2013 ; Beltz et al, 2022 ), it is an interesting question whether HC choice is also associated with femininity or masculinity. So far, two studies have investigated associations between HC-use and women’s gender role self-concept with inconsistent results: While one study demonstrates that HC-users rate themselves as more feminine compared to non-users ( Pletzer et al, 2015 ), the other study demonstrates no differences in the gender role self-concept of HC-users and non-users ( Nielson and Beltz, 2021 ).…”
Section: Introductionmentioning
confidence: 99%